Pelayanan Publik Penanganan Kasus Kekerasan Terhadap Perempuan Dan Anak (Studi Kasus Pada Kepolisian Sektor Maulafa) - Polin, Karin Angelin; Ena Mau, Alfred Omri; Benyamin, Rouwland A. (Universitas Pahlawan Tuanku Tambusai, 2025)
The Indonesian National Police is one of the institutions that provides public services, especially in the current era of globalization. With increasingly tight competition and numerous challenges, the police are required to deliver quality services that meet the needs of the community. Improving the quality of public services is absolutely necessary, considering the increasingly informed and responsive nature of society toward any deviations in public service, often voiced through print and electronic media. Data collection techniques used in this study include interviews, observation, and documentation. Data analysis in this research is carried out using triangulation techniques.Based on the research findings, it was concluded that the implementation of police services at Maulafa Sector Police has not yet developed efficiently and thus must strive to perform its duties in the best possible manner to provide comfort and satisfaction to the community. The police must offer effective services that result in excellent public service, which in turn would indicate that the service is productive. Therefore, in efforts to achieve high-quality service, it is only fitting that the police improve their service quality in accordance with regulations concerning the enhancement of public service quality by government officials.